Developing Students’ Worksheets based on the Inquiry-Flipped Classroom Learning Model to Improve Argumentation Skills - Yultari Ramadani; Pujiriyanto Pujiriyanto; Suwartia Suwartia; Minarni Minarni (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to develop students’ worksheets (LKPD) by the syntax of the inquiry-flipped classroom model to improve argumentation skills using the ADDIE development model (analysis, design, development, implementation, and evaluation). In blended learning, the teacher provides material through several platforms that support online learning. Accordingly, we need an LKPD to help students understand the material independently and improve students' argumentation skills. The research data was acquired by distributing questionnaires to validate design and material experts, teacher and student responses. The results of this study can be 85% per cent in the validation of the learning design with very valid criteria, and material validation got a score percentage of 86% with valid criteria. Based on the teacher's response test, the results obtained were 85.22% in the "practical" category, and the student's response test was 83.75% in the "practical" category. LKPD can improve the students' argumentation skills to levels 3-4.